RESPONSE YIELD WHEAT AND ITS COMPONENTS TO ABA UNDER EFFECT OF WATER STRESS - & Hashim, Ahmad (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Two field experiments were carried out at field crop research station- Abu-Ghraib- agricultural researches office during 2014-2015 and 2015-2016 to investigate effect of  irrigation deficiency quantities and ABA concentrations soaking and spraying on yield, its components of bahooth 10 wheat cultivar. Split plot arrangement by RCBD with three replicates for each experiment. First trial included for water irrigation quantities which control treatment (50% water depletion from available water), 70% and 40% from control treatment as well as rainy treatment (germination irrigation + rainfed) which occupied main plots while ABA soaking concentration (0, 1, 2, and 3) micromoles which occupied sup plots. Second experiment included same irrigation treatments which occupied main plots while ABA spraying concentration (0, 30, 60 and 90) micromoles occupied sub plots. The results of first experiment revealed there is no significant differences between the control treatment and 70% of the control for the number of spikelet per spike 18.79 and 18.45 spikelet Spike-1, number of spike 331.99 and 330.54 spike m-2, grain yield 4.73 and 4.74 ton ha-1 as average for both season respectively. The results of second experiment showed that control treatment attained the highest values of number of spike 328.25 and 333.92 spike m-2, grain yield 4.97 and 5.11 ton ha-1 for both season respectively, but didn’t differ 70% from control treatment. Concentrations soaking and spraying of ABA affect significantly most of studied traits. 3 micromoles Soaking concentration gave the highest values for number of spikes 309.00 and 310.25 spike m-2, number of grain per spike 49.81 and 51.18 grain Spike-1, grain yield 3.62 and 3.97 ton ha-1 for both season respectively, spraying with ABA at 60 micromole concentrations gave the average number of spike 326.00 and 332.00 spike m-2, grain yield 3.85 and 4.18 ton ha-1 for both season respectively with no significant difference with 90 micromole concentration which gave the highest values. The interaction between irrigation and ABA (soaking and spraying) showed a significantly effect on most characteristics yield and its components. Therefore can be conclude to capability of irrigation with 70% from full irrigation without signification effect in grain yield, as well as can be treat plant wheat with ABA concentration 3 and 60 micromoles soaking and spraying respectively to improve their ability to tolerance water stress.